上古汉语的施用操作 ：以《左转》= Applicative in archaic Chinese illustrated by Zuo Zhuan - 冯倩婷 Foong, Sin Theng (2013)
“Word-Class Shift” is a topic that researchers would definitely involve when discussing about Archaic Chinese grammar, and “Special Verb-Object Constructions” is a closely related topic to “Word-Class Shift”. Researchers have also created various classifications for “Special Verb-Object Constructions”, depending on the semanticrelations between the verb and object, or the semantic role that the object takes on. However, despite the various classifications that researchers have listed, it still unclear as to how the different verbs and different objects come about taking on different “Special Verb-Object Constructions”. Besides, many researches in the Archaic Chinese grammar field have agreed that an *-s suffix, which serves as a morphological process to the verb, exists in Archaic Chinese. But past researches on “Special Verb-Object Constructions” has never taken the *-s suffix construction into discussion. And these are questions we ought to seek an answer to. According to how researchers define “Special Verb-Object Constructions”, it seems that they agree that what differs them, is that unlike the “normal” verb-object constructions where the “patient” semantic role takes up the direct object function, non-core arguments take up the direct object function in “Special Verb-Object Constructions”. This definition that researchers have is very much similar to what Typology discuss in Applicative. This paper, therefore, attempts to review what past researches have defined as “Special Verb-Object Constructions” based on the typological Applicative, illustrated by ZUO ZHUAN, hoping to seek the regularity of Applicative Constructions in Archaic Chinese.